2013
DOI: 10.1016/j.pain.2013.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of paclitaxel on transient receptor potential vanilloid 1 in rat dorsal root ganglion

Abstract: Peripheral neuropathy is a common adverse effect of paclitaxel treatment. To analyze the contribution of transient receptor potential vanilloid 1 (TRPV1) in the development of paclitaxel-induced thermal hyperalgesia, TRPV1 expression in the rat dorsal root ganglion (DRG) was analyzed after paclitaxel treatment. Behavioral assessment using the tail-flick test showed that intraperitoneal administration of 2 and 4 mg/kg paclitaxel induced thermal hyperalgesia after days 7, 14, and 21. Paclitaxel-induced thermal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
95
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(104 citation statements)
references
References 33 publications
9
95
0
Order By: Relevance
“…The incidence of paclitaxel-induced neuropathy ranges from 20% to 70% of patients (24,25). Mechanisms include disruption of axonal transport (26,27), mitochondrial damage (28)(29)(30), altered ion channel activities (31), and neuronal inflammation (32,33). Here we screened three compound libraries, including ion channel ligands, GABA and REDOX libraries, for the discovery of potential neuroprotective drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of paclitaxel-induced neuropathy ranges from 20% to 70% of patients (24,25). Mechanisms include disruption of axonal transport (26,27), mitochondrial damage (28)(29)(30), altered ion channel activities (31), and neuronal inflammation (32,33). Here we screened three compound libraries, including ion channel ligands, GABA and REDOX libraries, for the discovery of potential neuroprotective drugs.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that formalin-induced pain is evoked by the activity of numerous mediators, channels, and receptors (Santos and Calixto, 1997;Coste et al, 2012), as well as nerve fiber types (Rios et al, 2013) and signaling pathways (Coste et al, 2012). Paclitaxel in turn is a chemotherapeutic agent, which causes toxic painful neuropathy and pain that are usually resistant to analgesic drugs (Nieto et al, 2012;Hara et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…TRPV1 (Hara et al, 2013), TRPV4 (AlessandriHaber et al, 2004;Levine and Alessandri-Haber, 2007), TRPA1-and TRPV4-mediated glutathionesensitive mechanisms (Materazzi et al, 2012) might be involved in the development and maintenance of paclitaxel-evoked neuropathic pain, although other molecules, such as sigma-1 receptors (Nieto et al, 2012), cannabinoid receptors (Authier et al, 2009), calcium channels (Authier et al, 2009) and CCL2 chemokines (Pevida et al, 2013), are also considered.…”
Section: Introductionmentioning
confidence: 99%
“…chemotherapy-induced neuropathy | neuropathic pain | TRPV1 | telmisartan | oxidized lipids R ecent studies identified members of the transient receptor potential-family of ion channels (TRPV1, TRPA1, and TRPV4) as contributors to both mechanical and cold allodynia during oxaliplatin and paclitaxel-induced neuropathy (1)(2)(3)(4)(5). Activation or sensitization of TRPV1 and TRPA1 can lead to enhanced release of CGRP and substance P, both of which can cause neurogenic inflammation and recruitment of T cells (6,7).…”
mentioning
confidence: 99%